2001
DOI: 10.1046/j.1365-2923.2001.00768.x
|View full text |Cite
|
Sign up to set email alerts
|

Publication pattern of medical theses, France, 1993-98

Abstract: Most French medical theses are not made available to the scientific community. In the European context, where medical training and qualification have to be standardized, our study provides a simple method of assessing that publication objectives of thesis research are met. Further research is needed to explore the educational value of medical professional theses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
2
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 2 publications
1
46
2
3
Order By: Relevance
“…In Germany, it is mandatory for medical students to submit a thesis outlining the results of a research project in order to graduate with the title "Doctor" [30]. This requirement has also been reported in Peru, Finland, France and some U.S. universities such as Yale [24,27,76,94]. The AAMC 2013 Graduation Questionnaire shows that 68.2% of US medical graduates participated in a research project with a faculty member on a mandatory or volunteer basis and 41.7% co-authored a research paper [7].…”
Section: Resultsmentioning
confidence: 99%
“…In Germany, it is mandatory for medical students to submit a thesis outlining the results of a research project in order to graduate with the title "Doctor" [30]. This requirement has also been reported in Peru, Finland, France and some U.S. universities such as Yale [24,27,76,94]. The AAMC 2013 Graduation Questionnaire shows that 68.2% of US medical graduates participated in a research project with a faculty member on a mandatory or volunteer basis and 41.7% co-authored a research paper [7].…”
Section: Resultsmentioning
confidence: 99%
“…Studies of text similarity in abstracts and titles have provided interesting approaches to detect papers derived from theses (Salmi et al 2001;Benotmane et al 2012;Caan and Cole 2012), although they have not been able to discern with clear evidence outputs emananting from theses. However, on the basis of full-text comparison of theses and articles of the same author, the Discussion section has demonstrated to be the essential part to identify the derivative articles.…”
Section: Discussionmentioning
confidence: 99%
“…That means, on average, that 81.3 % of authors published related papers before or during the year of the thesis completion. Other authors reported publications of medical students using different criteria, such as: Salmi et al (2001) on French medical theses, with any article registered before the thesis submission, 14 papers (27.5 %) in the year of presentation, with a cumulative proportion of 49.0 % of papers having been published after 2 years. Dhaliwal et al (2010) on medical theses in an Indian university did not include the possibility of articles derived before or during the year of the thesis completion, and Larivière (2012) in a study about the contribution of Canadian PhD students in peer reviewed students revealed that 63 % of doctoral students in health contributed to at least one paper during their doctorate, although any relationship with their PhD thesis was reported.…”
Section: Discussionmentioning
confidence: 99%
“…5 Although these theses are recognized by the scientific community as official scientific documents, theses are seldom read by more than a few scientists, because they are usually available only in University libraries or in the Library of the Council of Higher Education, written in Turkish language only, and not indexed in international databases. Research results, which are published in relevant literature, will become more readable and easy accessible through secondary publication to all scientists.…”
Section: Discussionmentioning
confidence: 99%